Grupo sala de espera na unidade de terapia intensiva: acolhimento dos familiares pela enfermeira - Moreira, Débora de Araújo (2011)
The Intensive Care Unit (ICU) is a local in the hospital for receiving patients with injuries to life, whether clinical or surgical. During the time of admission of patients, their relatives have exalted feelings of anxiety, fears and doubts arising from separation and imminent risk of loss of their relative. Own rules and routines of the ICU, the restricted access of family in the unity and the unknowledge of the environment can exacerbate fear about functioning, care and interventions provided. This study aimed to: Develop a waiting room group to welcome family members of ICU patients as a strategy for humanization of assistance; Describe the stages of group process in the family host; analyze the group approach as a tool in the host of family of ICU patients. Qualitative research, descriptive and exploratory methodological, based in the “Group process for nurses” proposed by Maxine Looms (1979). The study was performed in the waiting room of the Intensive Care Unit (ICU) in a public hospital located in Fortaleza-Ceará, Brazil. During the period from June to September 2011, the study respondents were family members who had relatives admitted into Intensive Care Unit. The inclusion of family members was conditional on signing the consent form. In the first stage, we made 37 individual interviews to know family needs about having a family member in the ICU. In the intervention phase with waiting room groups we had on average 20 visitors per day. The individual evaluation phase of these groups was performed with 26 relatives. The results showed that the family members need information of health status and diagnosis of their patient and this information should be clear and with less technical language. Professionals should be respectful and truthful when the information is provided. The groups were conducted following systematic guidelines and explaining the ICU routines. In the end we held orientations of questions of the group itself. In the evaluation of the groups found that the family felt welcomed and attended carefully to the proposed activities. The guidelines regarding handwashing and the possibility to talk / touch the patient were identified in speeches as relevant topics covered in the group. The information received on these activities generated change in the behavior of the family at the time of visit. The host is a strategy referenced successfully in serving families. The study showed that the performance of an educational group in the waiting room of the ICU, coordinated by nurses, can reduce unknownledge and anxiety of family members during the visit, not only to the patient, the nature and causes of disease, but also risks related to therapy. As well as encourage and motivate families to cope with the pain of hospitalization of their relative, thus helping to reduce the distress and suffering of all involved. Health promotion in the tertiary level, with the participation of the family becomes effective and concrete the Humanization of the hospital, with the expansion of its care and scientific knowledge, in addition to inpatient and techniques implemented them.